Energy-Aware Network-on-Chip Application Mapping Based on Domain Knowledge Genetic Algorithm - Yin Zhen Tei; Yuan Wen Hau; N. Shaikh-Husin; Trias Andromeda; M. N. Marsono (IAES Indonesia Section, 2014)
This paper addresses energy-aware application mapping for large-scale Network-on-chip (NoC). The increasing number of intellectual property (IP) cores in multi-processor system-on-chips (MPSoCs) makes NoC application mapping more challenging to find optimum core-to-topology mapping. This paper proposes an application mapping technique that incorporates domain knowledge into genetic algorithm (GA) to minimize the energy consumption of NoC communication. The GA is initialized with knowledge on network partition whereas the genetic crossover operator is guided with inter-core communication demands. NoC energy estimation is based on analytical energy model and cycle-accurate Noxim simulation. For large-scale NoC, application mapping using knowledge-based genetic operator saves up to 28% energy compared to the one on conventional GA. Adding knowledge-based initial mapping speeds up convergence by 81% and further saves energy by 5% compared to only knowledge-based crossover GA. Furthermore, cycle-accurate simulations of applications with traffic dependency show the effectiveness of the proposed application mapping for large-scale NoC.